2012
DOI: 10.1021/am201292a
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent, Freestanding Composite Films of Au15 for Specific Metal Ion Sensing

Abstract: A highly luminescent freestanding film composed of the quantum cluster, Au(15), was prepared. We studied the utility of the material for specific metal ion detection. The sensitivity of the red emission of the cluster in the composite to Cu(2+) has been used to make a freestanding metal ion sensor, similar to pH paper. The luminescence of the film was stable when exposed to several other metal ions such as Hg(2+), As(3+), and As(5+). The composite film exhibited visual sensitivity to Cu(2+) up to 1 ppm, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 33 publications
1
68
0
2
Order By: Relevance
“…3). 21,23,99 For instance, Zhang et al developed a facile method of immobilizing BSA-Au NCs into polyelectrolytes to obtain the Au NC-containing film for the detection of Cu 2+ . The visual detection limit of Ag + was determined to be 25 ppm and even to be lower (5 ppm) for Hg 2+ and Pb 2+ .…”
Section: Chao Lumentioning
confidence: 99%
See 1 more Smart Citation
“…3). 21,23,99 For instance, Zhang et al developed a facile method of immobilizing BSA-Au NCs into polyelectrolytes to obtain the Au NC-containing film for the detection of Cu 2+ . The visual detection limit of Ag + was determined to be 25 ppm and even to be lower (5 ppm) for Hg 2+ and Pb 2+ .…”
Section: Chao Lumentioning
confidence: 99%
“…99 The glutathione (GSH)-stabilized Au NCs were incorporated into the film via the combination of the amino group from chitosan with the carboxyl group from GSH. 99 The glutathione (GSH)-stabilized Au NCs were incorporated into the film via the combination of the amino group from chitosan with the carboxyl group from GSH.…”
Section: Chao Lumentioning
confidence: 99%
“…George et al demonstrated the feasibility of using gold nanoclusters in a device arrangement using chitosan as the film matrix (Figure ). The Au 15 quantum nanoclusters were encapsulated in a cyclodextrin, aiming to increase both chemical and thermal stability of the clusters, before being dispersed on a dried chitosan film soaked with sodium citrate to enhance the film strength.…”
Section: Chitosan‐derived Luminescent Materialsmentioning
confidence: 99%
“…(Adapted from Ref. , with permission from American Chemical Society). [Color figure can be viewed in the online issue, which is available at http://wileyonlinelibrary.com.…”
Section: Chitosan‐derived Luminescent Materialsmentioning
confidence: 99%
“…Particle size and shape have played crucial roles in optimizing the performance of commercial applications, such as air purification systems, new generations of automobile exhaust catalysts, nanoelectronics, photothermal cancer therapy, and various sensors [279][280][281][282][283][284][285]. The surface plasmon resonance phenomenon plays a crucial role in many sensors reported in the literature, as it allows tuning of the sensor properties via both particle size and shape [240,279,286,287].…”
Section: Nanoplatesmentioning
confidence: 99%